Modern options of application of domperidone in gastroenterology - A. A. Sheptulin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The aim of review. To carry out analysis of the publications devoted to application of prokinetic drug domperidone (D) at various gastroenterological diseases.Key points. Literature data demonstrate, that dopamine receptor antagonist D is effective drug for treatment of such diseases, as functional dyspepsia, diabetic and idiopathic gastroparesis, gastroesophageal reflux disease (within combined treatment modes), and for relief of nausea and vomiting, caused by cytotoxic agents as well. Side effects at application of D are determined by risk of hyperprolactinemia, which rarely clinically relevant.Conclusion. Domperidone can be successfully applied for treatment of gastroenterological diseases accompanying primary or secondary disorders of stomach and duodenum motility.